A MODERN APPROACH TO THE ACCURACY OF MATHEMATICAL PROBLEM-SOLVING ABILITY ASSESSMENT: GENERALIZED PARTIAL CREDIT MODEL - Aditya Prayogi; Mujahidawati; Ilham Falani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract This study aims to measure students' mathematical problem-solving ability using the Item Response Theory (IRT) approach with the Generalized Partial Credit Model (GPCM). The research was carried out in North Bahar District, Muaro Jambi Regency, by involving all grade IX junior high school students in the even semester of the 2024/2025 school year as a sample through total sampling techniques. The test instruments were compiled and analyzed based on five main stages, including testing, scoring, and data processing and analysis using PARSCALE 4.1 software. The results of the analysis showed that the instruments used met the assumption of unidimensionality, which at the same time indicated the fulfillment of the assumption of local independence and parameter invariance. The model fit test produces a value indicating that the GPCM model matches the empirical data. Student ability estimates show a distribution that is close to normal, with most students being at moderate to slightly below average ability levels. The parameters of the question items showed high differentiating power and moderate difficulty, while the test information function showed the effectiveness of the instrument in measuring students' ability at average ability. In conclusion, the GPCM model is effectively used in measuring students' mathematical problem-solving abilities validly, accurately, and thoroughly.